A A RETROSPECTIVE STUDY INJURIES IN SLEMAN BADMINTON PLAYERS - nurwahida puspita sari (LPPM Universitas Abdurrab, 2019)
Background. Sports injury is a problem that arises in a person after doing physical activity or exercise both when exercise and match,it can happen suddenly and difficult to avoid. Sports injuries for a professional athlete can result in losing time following training and matches and decrease achievement. Therefore, information about sports injuries in badminton to avoid and minimize injury is needed. Purpose. To understand the demographics, investigate the types of injuries, and find out the 5 types of injuries that are most common in badminton players. Research methods. This study is a retrospective study with a survey method. Results. The results of this study show the demographics of badminton players in Sleman based on age dominated by 11-16 years old players as with 97 players (58%), for sex dominated by men with 101 players (60%), based on Body Mass Index (BMI) dominated normal in 117 players (68%). The most common type of injury that occurs is soft tissue injury consisting of bruising, strain, sprain, overstretch, and for hard tissue injury consisting of dislocation. Five most common badminton injuries in order are: shoulder overstretch, knee injury, ankle strain, tennis elbow and hamstring strain.